Trading faces: The 'Korean Look' and medical nationalism in South Korean cosmetic surgery tourism. (15th June 2017) - Holliday, Ruth; Cheung, Olive; Cho, Ji Hyun; Bell, David
Abstract: This paper addresses the growing phenomenon of cosmetic surgery tourism through a focus on the development of this industry in South Korea. Unlike many discussions of this topic, the paper decentres dominant narratives based on west‐goes‐east or north‐goes‐south journeys. Instead, we look at regional flows by exploring the experiences of Chinese patients travelling to South Korea in search of facial cosmetic surgery – procedures often referred to as the 'Korean Look' and associated with exported Korean popular culture. We focus on the contested understandings of the motives for and outcomes of this surgery between Korean surgeons and Chinese patients, documenting one example of the cultural investments and (mis)understandings that can impact on the experiences of medical tourists as they travel across national borders in search of treatment. We situate the development of cosmetic surgery tourism in Korea in the context of a discourse we call 'medical nationalism', showing how surgeons in particular reproduce this discourse in terms of pride in their contribution to the economic and reputational success of South Korea on a world stage. However, we demonstrate finally that, as a privatised, feminised and trivialised form of medicine, cosmetic surgery will always fail to deliver in this respect.